How does Santa go down the chimney? - Barnett, Mac (Candlewick Press, 2023)
"When Santa arrives at a child's house on Christmas Eve, does he go down the chimney feetfirst or headfirst? What if he gets stuck? What if there's no chimney? Maybe he slides under the door, as thin as a piece of paper? Or is it possible he pours himself through the faucet? What happens once he's inside? Whether it's shape-shifting or impromptu laundry use, Mac Barnett's iconic talent for earnest deadpan humor and Jon Klassen's irresistibly funny art honor the timeless question with answers both ridiculous and plausible, mounting in hilarity as the night continues"--